2008
DOI: 10.1211/jpp.60.5.0001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of human pharmacokinetics—biliary and intestinal clearance and enterohepatic circulation

Abstract: The main objective was to evaluate and propose methods for predicting biliary clearance (CL bile ) and enterohepatic circulation (EHC) of intact drugs in man. Another aim was to evaluate to role of intestinal drug secretion and propose a method for prediction of intestinal secretion CL (CL i ). Animal data poorly predict the CL and CL bile of biliary excreted drugs, and the suggested molecular weight threshold for bile excretion as the dominant elimination route does not seem to hold. Active transport, low met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 62 publications
4
20
0
Order By: Relevance
“…Moreover, intestinal secretion is not regarded as a major route of drug elimination. [178,179] Thus, the inhibition of the enterocytic influx via OSTa/b is probably not of concern with regards to DDIs. However, OSTa/b is also an intestinal basolateral absorptive transporter (along [165,168] 4.0/4.6 a Simvastatin [164] 85 a Tipranavir [165] 0.9 a OATP3A1_v1 (OATP-D)…”
Section: Oatp1a2 (Oatp-a)mentioning
confidence: 99%
“…Moreover, intestinal secretion is not regarded as a major route of drug elimination. [178,179] Thus, the inhibition of the enterocytic influx via OSTa/b is probably not of concern with regards to DDIs. However, OSTa/b is also an intestinal basolateral absorptive transporter (along [165,168] 4.0/4.6 a Simvastatin [164] 85 a Tipranavir [165] 0.9 a OATP3A1_v1 (OATP-D)…”
Section: Oatp1a2 (Oatp-a)mentioning
confidence: 99%
“…Biliary excretion (BE) is a major elimination pathway for many drugs and/or their metabolites and has a significant impact on exposure and pharmacological and toxicological effects of drugs (Gregus and Klaassen, 1987;Fagerholm, 2008). Estimating its contribution to the total systemic clearance is thus extremely valuable for predicting clinical pharmacokinetics and understanding the possible mechanisms of hepatobiliary toxicity and potential drug-drug interactions (DDIs) (Lavé et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, Wang and Prueksaritanont (35) reported that human CL of therapeutic proteins can be predicted reasonably well by simple allometric scaling with a fixed exponent of 0.8. On the other hand, as with tubular and intestinal secretion, reabsorption, and metabolism, the accurate prediction of renal (CL R ) and bile clearance (CL bile ) using SA is difficult (19,20). A coefficient of determination (r 2 ), which is obtained from a linear regression of log-transformed animal body weights and the corresponding CL, has been reported in most allometric scaling studies.…”
Section: Simple Allometrymentioning
confidence: 99%
“…More effort is required to establish the in vitro/in vivo relationship for active secretion and to scale in vitro kidney microsomal data to in vivo metabolic clearance. Similarly, challenges posed by active transport, enterohepatic circulation, and metabolism have resulted in very few attempts to use physiologically based approaches to predict biliary and intestinal clearance, and the predictability is poor (19). One step to improve the prediction of biliary and intestinal clearance is to identify the interspecies differences in expression and activity of hepatic/bile and intestinal transporters and metabolizing enzymes.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation